FUNDAMENTAL PRINCIPLES OF THE MODEL OF PARTICIPATORY, PAYABLE, PROFITABLE, POTENT, INSURED EDUCATION SYSTEM (IESM) - Çelikhan, Seniha (European Scientific Journal, ESJ, 2014)
In the educational field, there is a need for a system which should become effective, useful and easily affordable and should include user participation. This need was the main reason; the author has designed the model named â€œInsured Education System Model - IESMâ€. The IESM is based on the principal which expenditures of education in each expenditure entry level will not be paid by the person itself. The insurance foundations are established to cover the educational expenditures of the buyers. Suggested model brings an auto-control to the mechanism and from the cycle IESM generates, the educational insurance foundations, educational institutions, buyers and households get benefits. Furthermore, IESM will increase the quality of service, educational system, employment and numbers of students. The result will be the decrease of the cost of the service. In this article, the fundamental principles of the model explained and frequency analysis used to determine the potential participation to IESM. The participation to IESM survey was more than % 50. The result of frequency analysis shows that IESM is an applicable model.